Ludwig van Beethoven, half portrait, three-quarter profile - Unknown:::Creator::::::::::::; Binenbaum, Lazar, 1876-before 1953 (artist):::Contributor::::::::::::
Anonymous engraving from the first half of the 20th century, based on the painting of Beethoven by Lazar Binenbaum.